(untitled) (Wudil Journal of Science and Technology Education, 2025)
Global warming and climate change are factors that leads to increase in droughts.Drought impairs plant growth and development consequently affecting crop yield thus plants develops certain measures that leads to adaptation of the drought stress for better plant growth under the stress condition. The effect of drought stress on osmolytes (glycine betaine and carbohydrate) and chlorophyll concentrations was studied in three cowpea varieties.The experiment was conducted between June to October 2019 at the greenhouse of Faculty of Agriculture, Bayero university, Kano. Two cowpea varieties drought tolerant (Dan”ila) and drought susceptible (TVU 7778) were obtained from IITA Kano and a local variety from a local market in Kano. The seeds were sown in plastic containers arranged in a completely randomized design. Each pot was irrigated to field capacity every other day with borehole water and water deficit was introduced at six weeks after sowing by totally withholding irrigation for a period of two weeks. After the stress treatment, irrigation was resumed for five days to assess recovery. Plant leaves samples were collected at 0, 5, 10 and 15 days drought and 5 days after resumption of irrigation (recovery). Results showed a significant increase in the concentration of carbohydrate and glycine betaine as the stress period increased and significant decrease at the re-watering period in the drought-tolerant and local varieties. However, there was a significant decrease in the concentration of chlorophyll in all the three varieties studied as the stress period increased. Osmolyte and chlorophyll played a role in the drought response of cowpea.